Application of Christian Religious Education Teacher Leadership to Realize Sunday School Quality at the Batu Hidup Christian Church, Muara Karang, Jakarta - Krisna Karolina Tafetin; Christian Ade Maranatha; Ester Agustini Tandana (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2022)
Christian Religious Education Teachers (CRE) are educators and shapers of behavior for children to have and emulate the character of Christ. Christian Religious Education (PAK) teachers have the right to provide effective teaching, for every child who is committed to accepting Jesus Christ as Lord and Savior. This is addressed to the Sunday School children of the Living Stone Christian Church (GKBH). The purpose of this study was to analyze and describe the implementation of Christian Religious Education teacher leadership to realize Sunday School quality at the Batu Hidup Muara Karang Christian Church. The method used is the method of library research and observation accompanied by structured interviews from the research site. Data and information obtained from research results, literature (library), and other sources in the form of books, articles and even journals were obtained. The results of this study at the Sunday School at the Batu Hidup Christian Church in Muara Karang, show that the leadership of the Sunday School teachers has been well managed. The teaching process uses props, the teacher is friendly and teaches patiently in dealing with the nature of children. Other additional activities include drawing, ice breaker, and coloring so that children don't get bored in learning. Guru Pendidikan Agama Kristen (PAK) adalah pendidik dan pembentuk perilaku bagi anak-anak agar memiliki dan meneladani karakter Kristus. Guru Pendidikan Agama Kristen (PAK) berhak untuk memberikan pengajaran yang efektif, bagi setiap anak-anak yang berkomitmen untuk menerima Yesus Kristus sebagai Tuhan dan Juruslamat. Hal ini ditujukan kepada anak-anak Sekolah Minggu Gereja Kristen Batu Hidup (GKBH). Tujuan penelitian ini adalah untuk menganalisis dan mendeskripsikan implementasi kepemimpinan guru Pendidikan Agama Kristen untuk mewujudkan mutu Sekolah Minggu di Gereja Kristen Batu Hidup Muara Karang. Metode yang digunakan adalah metode penelitian kepustakaan serta observasi yang disertai wawancara terstruktur dari tempat penelitian. Data dan informasi yang diperoleh dari hasil penelitian, literatur (kepustakaan), dan sumber-sumber lain berupa buku, artikel bahkan jurnal yang diperoleh. Hasil penelitian di Sekolah Minggu di Gereja Kristen Batu Hidup Muara Karang ini, menunjukkan bahwa kepemimpinan guru Sekolah Minggu telah di terapakan dengan baik. Proses pengajarannya menggunakan alat peraga, guru ramah dan mengajar dengan penuh kesabaran dalam menghadapi sifat anak-anak. Aktivitas tambahan lainnya berupa menggambar, Ice breaker, dan mewarnai sehingga anak-anak tidak jenuh dalam belajar.